A Proposed Vision for Editing News Forms - Faker, Khalel Ibraheem (ALBAHITH ALALAMI, 2018)
This research deals with a very important subject as it tries to change the theoretical and scientific heritage and some professional rules adopted in the newsroom. Most media students have difficulties in writing news for press correctly. The researcher tries to identify the compatibility of what is published in local news agencies with professional and academic standards. The research finds detailed editorial rules for a number of news formats which will play an important role in writing news for press easily, especially for the beginners and newcomers. Also, it discovers a new fact denying the beliefs of some researchers and writers in not having news conclusion in news edited according to the inverted pyramid pattern. The researcher finds that the news of the sample subject to research lacks diversity because most of them are written according to the inverted pyramid pattern with absolute exclusion of the rest of the news templates, especially the gradual pattern.